Intensi Perilaku Mahasiswa dalam Mengadopsi Mobile Banking dengan Pandemi Covid-19 sebagai Variabel Moderator - Popy Novita Pasaribu (Neolectura, 2021)
The phenomenon of accepting non-cash applications, including banking applications such as mobile banking, is reinforced by the Covid-19 pandemic, which is accelerating towards a digital society. The purpose of the study was to see whether the relationship between UTAUT2 factors and behavioral intentions of mobile banking adoption was moderated by the Covid-19 pandemic among young people, especially among students from private universities in DKI Jakarta. Sampling was done purposively and questionnaires were distributed online via Google Form. The sample collected in the first week of April 2021 was 114, but those that matched the criteria of 102 respondents. Data processing was carried out by regression analysis with the moderator variable assisted by the SPSS 26.0 application. The results of the regression analysis by looking at the Sig F Change resulted in a value above 0.05, namely the Covid-19 pandemic variable was not proven to significantly moderate the Utaut2 factors with Behavioral Intentions to Adopt Mobile Banking by private students in DKI Jakarta.